Quantification of onion (Allium cepa L.) evapotranspiration and crop coefficient via weighable lysimeter under semi-arid climate of Melkasa, Ethiopia - Nigusie Kebede; Mekonen Ayana; Boja Mekonnen (Heliyon)
In response to the growing challenge of water scarcity in agriculture, efficient irrigation planning and management have become increasingly essential. A critical component of this is determining the precise water requirements of crops. This study was conducted at Melkasa Agricultural Research Centre in Ethiopia during February to May in 2023 and 2024 and focused on quantifying the water requirement and crop coefficient of onion (Allium cepa L.), Nafis variety. Using weighable lysimeters, the study measured field-level water balance components, with crop evapotranspiration calculated through the water balance equation. The CROPWAT model and meteorological data from a station located nearby were used to estimate reference evapotranspiration. The results indicated that the pooled seasonal crop evapotranspiration was 460.27 mm, while the reference evapotranspiration for the same period was 509.18 mm. The average crop coefficient values were determined to be 0.68, 0.89, 1.03, and 0.86 for the initial, developmental, mid-, and late-season stages, respectively. Additionally, a third-order polynomial equation was established to predict the values of the crop coefficient based on the number of days after transplanting. These findings offer valuable insights for improving water resource use efficiency and optimizing irrigation scheduling for the production of onion, particularly in regions like Melkasa, where neither field-based measured data nor site-specific validated estimation methods are lacking.